A smart device for label-free and real-time detection of gene point mutations based on the high dark phase contrast of vapor condensation1. Issue 19 (7th October 2015) - Zhang, Junqi; Fu, Rongxin; Xie, Liping; Li, Qi; Zhou, Wenhan; Wang, Ruliang; Ye, Jiancheng; Wang, Dong; Xue, Ning; Lin, Xue; Lu, Ying; Huang, Guoliang
<x xml:space="preserve">Abstract</x> A smart device for label-free and real-time detection of gene point mutation-related diseases was developed based on the high dark phase contrast of vapor condensation.